SEEDLING PRODUCTION OF FRUIT AND ORNAMENTAL SPECIES TO THE USE OF WEED HORMONE (Cyperus rotundus) (Nucleus, 2017)
Currently, the great demand for fruit and ornamental plants have generated the need for production of healthy and vigorous seedlings. Some plants, such as purple nutsedge (Cyperus rotundus) produce hormones that can induce rooting cuttings, allowing its spread. The objective was to evaluate the spread of jabuticaba (Myrciaria cauliflora), guava (Psidium guajava) and mini ecsoria (Ixoria coccinea) by cuttings, evaluating the effect of concentrations of butyric acid (IBA) and extracts of tubers of purple nutsedge (Cyperus rotundus) in these species. Two experiments were conducted. The first experiment was conducted in a completely randomized design with a factorial 2 x 2 x 5, involving two species (guava and jabuticaba), two treatments (IBA and aqueous extract of purple nutsedge) with five concentrations of both treatments (25, 50, 75 and 100%) with five replicates. The second experiment also included in experimental design, involving mini ecsoria factorial scheme 5 x 2 x 2 with 2 treatments (IBA and aqueous extract of C. rotundus), five concentrations of both treatments (25, 50, 75 and 100%) and two conditions (controlled environment and natural environment), with five replicates. Both treatments with IBA or nutsedge, showed positive results on the number of shoots on the cuttings. For mini ecsoria, we observed similar results to the first experiment, with larger amounts of sprouts in a natural environment.